The Exploration of Body-Worn Video to Accelerate the Decision-Making Skills of Police Officers within an Experiential Learning Environment. (29th March 2017) - Richards, Pam; Roberts, Debbie; Britton, Mark; Roberts, Nathan
Abstract: Previous research has highlighted benefits of body-worn video (BWV) to support the work of police officers. The daily demands of policing require officers to make highly pressurized decisions (with associated rapid action) in unpredictable changing environments. It is important that new officers learn techniques of decision-making in a safe and controlled way, which minimizes the risk and harm to all parties while at the same time facilitating effective learning. While the benefits of experiential and immersive learning characterized by active participation have long been used in related professional disciplines, the application to police education has been under-explored. BWV can be used to identify decision-making cues from the environment and nurture pattern recognition, essential to the development of mental models within the officer's decision-making process. The article will therefore explore the application of BWV in the context of experiential immersive learning to accelerate police officers' decision-making.